Possible effects of air pollution and urbanization on visibility in the Kuala Lumpur-Petaling Jaya area. - Sham Sani, (Universiti Kebangsaan Malaysia, 1979)
The only available data from the Airport have been used to examine the effects of air pollution and urbanization on visibility in the Kuala Lumpur-Petaling Jaya area. Although evidence were still inconclusive, there appeared to be a slight trend of deteriorating visibility during the 1966-75 decade particularly in the visibility range of >32.0 km (>20 miles). The growth of urbanization and industrial development within and around Kuala Lumpur-Petaling Jaya coupled with the absence of any form of smoke control measures have probably been the major contributory factors.